2020
DOI: 10.3390/nu12072068
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Intakes and Musculoskeletal Function in Very Old Adults: Analysis of the Newcastle 85+ Study

Abstract: Background: Selenium is a trace element essential for health. Severe selenium deficiencies are associated with poor musculoskeletal (MSK) function. However, the effects of moderate deficiency on MSK function, especially in older adults, is unclear. Objectives: To determine the associations between selenium intake and MSK function in very old adults. Methods: Selenium intake at baseline and, hand-grip strength (HGS) and timed-up-and-go (TUG) at four phases over 5 years, were available in 791 participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 116 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…The oxidative stress subsequently impairs cartilage and further leads to OA. However, as indicated by Perri et al (17), low dietary selenium intake was common in the elderly. And the study by Wang et al (8) was carried out among participants over 50 years old and the elderly are prone to OA, which may bias the findings.…”
Section: Discussionmentioning
confidence: 93%
“…The oxidative stress subsequently impairs cartilage and further leads to OA. However, as indicated by Perri et al (17), low dietary selenium intake was common in the elderly. And the study by Wang et al (8) was carried out among participants over 50 years old and the elderly are prone to OA, which may bias the findings.…”
Section: Discussionmentioning
confidence: 93%
“…24 Lower serum selenium and dietary selenium are associated with lower muscle mass and poorer muscle function in older adults. 27,[47][48][49] The proposed mechanism of action of selenium to reduce reactive oxygen species, and therefore reduce the pro-resorptive drive to osteoclasts, was plausible. However, we saw no effect at all on markers of bone resorption.…”
Section: Resultsmentioning
confidence: 99%
“…Physical activity was assessed using a purpose-built questionnaire and validated by comparison with accelerometery ( 28 ) . Se intake (µg/d), total energy intake (kcal) and protein intake (g) were determined using the 24-h multiple pass recall ( 11 , 29 ) . Disease count was calculated using a selected list of chronic diseases (online Supplementary Material Table ) ( 24 ) .…”
Section: Methodsmentioning
confidence: 99%
“…To date, there is limited information on dietary intake of Se among very old adults. However, an earlier analysis using data from ≥ 85-year-olds ( n 791) from the Northeast of England who participated in the Newcastle 85+ Study found that over 50 % had dietary Se intakes below the lower reference nutrient intake ( 11 ) .…”
mentioning
confidence: 99%